THE INFLUENCE OF EXPERIENTIAL MARKETING AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY AT ATTAYA CAFÉ&RESTO - Manengal, Gloria F.; Lapian, Joyce S.L.H.V.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2022)
Customer loyalty is important in every business’s continuity. Experiential marketing and customer satisfaction are two factors that are important in the understanding of customer loyalty from a business destination, especially any food and beverage-based one. This study aims to figure out the influence of experiential marketing and customer satisfaction to customer loyalty of Attaya Café & Resto’s customers. Overall population in this research is all customers of Attaya Café & Resto’s and the chosen sample is 100 respondents. Data analysis uses multiple linear regressions analysis method. This research result proves that experiential marketing and customer satisfaction simultaneously have positive and significant influence customer loyalty of Attaya Café & Resto’s customers. Its’ management have to preserve and boost experiential marketing and customer satisfaction in this dining destination and deliberate other factors that influence the loyalty from Attaya Café & Resto’s customers. Keywords: Experiential marketing, customer satisfaction, customer loyalty